The Challenges And Difficulties Faced By Jordanian Teachers In Online Teaching During The COVID-19 Pandemic In Amman (Journal of Namibian Studies : History Politics Culture, 2024)
The research is centered on evaluating the challenges and difficulties encountered by Jordanian teachers in Amman during the transition to online teaching amidst the COVID-19 pandemic. This study aims to gain insights that could be beneficial for similar experiences in the future. The study's methodology involves a qualitative approach with a sample size of 105 teachers, evenly divided between male and female participants. It delves into various aspects of online teaching challenges faced by these educators, including technical skills, access to technology, workload, student engagement, and the efficacy of monitoring student progress. By exploring these areas, the research provides valuable insights into the experiences of teachers, significantly enhancing the understanding of how the pandemic has influenced the educational landscape in Jordan.